Existing Technologies Can Assist the Disabled. - Kirkpatrick, Keith (Communications of the ACM, 2016)
The article focuses on the availability of technology products for people with physical impairments including tablets, smartphones, and personal computers. Topics discussed include the development of applications and screen reader software such as OpenOffice and the Java platform, the statement of researcher Frederic Pollman on the development of HoverZoom mobile app, and the development of assistive robots for blind travelers.